2015
DOI: 10.1111/ijpp.12236
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with iron deficiency anaemia among hospitalised Lebanese infants

Abstract: Incidence of IDA among Lebanese infants is moderate and multifactorial. High maternal education level, urban residence, giving iron supplements to exclusively breastfed infants starting from 6 months of age, adequate family income and iron supplementation in both mother and infant are significant protective factors against anaemia in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…On the contrary, a study conducted in Nepal [32] and a systematic review [33] revealed that early introduction of complementary foods had improved hemoglobin concentrations of children. This study is consistent with a study conducted in northern Ethiopia [8], Lebanon [34], Brazil [35] and China [36]. Which reports that early introduction of solid or liquid foods is related with childhood anemia.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, a study conducted in Nepal [32] and a systematic review [33] revealed that early introduction of complementary foods had improved hemoglobin concentrations of children. This study is consistent with a study conducted in northern Ethiopia [8], Lebanon [34], Brazil [35] and China [36]. Which reports that early introduction of solid or liquid foods is related with childhood anemia.…”
Section: Discussionsupporting
confidence: 92%
“…The lowest prevalence of anemia was found among Saudi school-aged children and the elderly at approximately 12% [57,58]. …”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…The prevalence of anemia in children and adolescents ranges from 11.6% in Saudi school-aged children [60] to 39.6% in Egyptian preschool children [61]. As classified by the WHO, the prevalence of anemia, as a public health issue globally, describes a mild problem at 5%–19.9%, a moderate problem at 20%–39.9%, and a severe problem at ≥40%; most Arab Middle East countries fall within the category of moderate to severe deficiency [57,62]. …”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Since the fetus depends on the maternal iron level, higher risk women for iron deficiency with concomitant increased risk of anemia among newborn babies. Due to these, anemia in the newborn has serious public health issues in developing countries [11,12].…”
Section: Introductionmentioning
confidence: 99%